2017
DOI: 10.1002/ijc.30933
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adenoma detection on the benefit of faecal testing vs. colonoscopy for colorectal cancer

Abstract: Colonoscopy quality, as measured by adenoma detection rates, varies widely across providers and is inversely related with patients’ post-colonoscopy cancer risk. This has unknown consequences for the benefits of faecal immunochemical testing (FIT) versus primary colonoscopy screening for colorectal cancer. Using an established microsimulation model, we predicted the lifetime colorectal cancer incidence and mortality benefits of annual FIT versus ten-yearly colonoscopy screening at differing ADR levels (quintil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Detection of cancers was similar in the two intervention arms in the intention-to-screen and in the as-screened analysis, similar to the findings in the study by Quintero et al (1) but contrary to a Chinese study (6) where colonoscopy had a higher yield. However, polypectomy is the main effector in colorectal cancer prevention (22), and the different capacity of the SCREESCO study arms to find premalignant lesions is likely to have implications for the long term colorectal cancer mortality (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of cancers was similar in the two intervention arms in the intention-to-screen and in the as-screened analysis, similar to the findings in the study by Quintero et al (1) but contrary to a Chinese study (6) where colonoscopy had a higher yield. However, polypectomy is the main effector in colorectal cancer prevention (22), and the different capacity of the SCREESCO study arms to find premalignant lesions is likely to have implications for the long term colorectal cancer mortality (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…[5] In a recent modeling study by Meester at al, a 5% decrease in ADR was associated with a 12.3% and 13.3% increase in colorectal cancer incidence and mortality, respectively. [6] One potential driver of lower ADR is that, over the course of a day, an endoscopist may become fatigued and thereby detect fewer adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…Nine simulation models were identified, including three Cancer Intervention and Surveillance Modeling Network (CISNET) CRC models (CRC Simulated Population Model for Incidence and Natural History (CRC-SPIN) [ 14 , 24 , 30 , 31 , 42 ], Simulation Model of Colorectal Cancer (SimCRC) [ 14 , 24 , 30 , 31 , 36 , 42 ] and MIcrosimulation SCreening ANalysis-Colon (MISCAN-Colon) [ 14 , 20 , 21 , 22 , 24 , 25 , 29 , 30 , 31 , 35 , 36 , 37 , 38 , 39 , 42 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]), adenoma and serrated pathway to colorectal cancer (ASCCA) [ 12 , 19 , 26 , 27 , 28 , 43 ], Microsimulation-based colon modelling open-source tool (CMOST) [ 23 , 41 ], Colorectal Cancer and Adenoma Incidence and Mortality Microsimulation Model (CRC-AIM) [ 40 , 44 , 68 , 69 ...…”
Section: Resultsmentioning
confidence: 99%
“…In the pooled analyses, gFOBT screening leads to a MR of 17% with 95% confidence intervals (95% CI) of 8–25% [ 17 ], and that FS results in a MR of 28% (95% CI: 20–35%) [ 15 , 16 ]. The model studies showed 24–79%, 8–84%, 25–56%, 16–94%, and 55–81% CRC-specific MRs on biennial fecal immunochemical tests (FIT), biennial gFOBT, single FS, 10-yearly colonoscopy, and 5-yearly FS screening, respectively [ 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Adherence rates, adenoma detection rates and dwelling time were used in several model studies in the sensitivity analyses [ 10 , 13 , 19 , 23 , 40 , 41 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation